Changes in obstetric case fatality and early newborn mortality rates in hospitals after the implementation of the Expanding Maternal and Neonatal Survival program in Indonesia: Results from a health information system. (27th February 2019) - Ahmed, Saifuddin; Tholandi, Maya; Pedrana, Alisa; Zazri, Ali; Parmawaty, Nony; Rahmanto, Agus; Sethi, Reena
Abstract: Objectives: Case fatality rates (CFRs) are often used as the key indicator for the measurement of quality of care at hospitals. We examine the trends of obstetric CFRs and very early neonatal mortality rates at hospitals in selected districts of Indonesia after implementation of a facility‐based maternal and neonatal health intervention—the Expanding Maternal and Neonatal Survival (EMAS) program. Methods: Random‐effects Poisson regression models were fitted to routine facility data collected from 101 hospitals over approximately 4 years. Predicted incidence rates from the models were used for ascertaining the changes in CFRs and very early neonatal mortality rates during the EMAS intervention period. Results: The obstetric CFR from any maternal complications decreased significantly by 50% (adjusted incidence rate ratio [IRR] 0.50; 95% confidence interval [CI] 0.42–0.61) at hospitals after the implementation of the EMAS program. On average, the CFR decreased from 5.4 to 2.6 deaths per 1000 cases of obstetric complications admitted during the program period. The very early neonatal mortality rate (deaths within 24 hours of birth) decreased by 21% (IRR 0.79; 95% CI, 0.65–0.96). Conclusion: Our study suggests that overall obstetric case fatality and very early neonatal mortality rates—two indicators for tracking the quality of emergency obstetric care—decreased significantly at hospitals after the implementation of the EMAS intervention program in Indonesia. Abstract : Trends of obstetric case facility rates and very early neonatal mortality rates at hospitals in selected districts of Indonesia were assessed after implementation of the facility‐based Expanding Maternal and Neonatal Survival program.